A comparison of six outcome measures across the recovery period after distal radius fixation—Which to use and when?. (28th January 2021) - Fang, Christian; Fang, Evan; Yee, Dennis KH; Kwan, Kenny; Leung, Gladys; Leung, Frankie
Purpose: Many standardized outcome measures exist to measure recovery after surgical fixation of distal radius fractures, however, choosing the optimal instrument is difficult. We evaluated responsiveness, ceiling/floor effects, and criterion validity over multiple time intervals across a 2-year follow-up period for six commonly used instruments. Methods: A total of 259 patients who received open reduction and internal fixation for distal radius fractures between 2012 and 2015 were recruited. Patients were administered the Patient-Rated Wrist Evaluation ( PRWE ), Shortened Disabilities of the Arm, Shoulder and Hand questionnaire ( QuickDASH ), Green and O'Brien score (Cooney modification) ( CGNO ), Gartland and Werley score (Sarmiento modification) ( SGNW ), flexion-extension arc ( FEArc ), and grip fraction test ( GripFrac ) at 1.5, 3, 6, 12, and 24 months postoperatively. Responsiveness was evaluated by calculating standardized response means (SRM) and Cohen's d effect sizes (ES), and by correlating each instrument's change scores against those of QuickDASH and PRWE, which were also used as external comparators to assess criterion validity. Ceiling/floor effects were calculated for all measures at each time point. Results: SRM (1.5–24 months) were 1.81, 1.77, 1.43, 1.16, 2.23, 2.45 and ES (1.5–24 months) were 1.81, 1.82, 1.95, 1.31, 1.99 and 2.90 for QuickDASH, PRWE, CGNO, SGNW, FEArc, and GripFrac respectively. Spearman correlation coefficients against QuickDASH at 24 months were: 0.809, 0.248, 0.563, 0.285, and 0.318 for PRWE, CGNO, SGNW, FEArc, and GripFrac respectively. Significant (>15% of patients reaching maximum score) ceiling effects were observed before 6 months for PRWE and SGNW . Conclusions: Our evidence supports the use of QuickDASH, PRWE, FEArc and GripFrac up to 6 months postsurgery, and QuickDASH and PRWE after 6 months. Level of evidence: Level II.